OPTICS IN THE GLOBAL CHANGES OF ENVIRONMENT - Sergei Avakyan
The results of the works performed in the field of the most actual problems of physics and optics of the solar–terrestrial links have been analyzed. This is the problem of energy in the ionospheric physics, considered because space monitoring of the solar radiation fluxes and the precipitating corpuscular (mainly electrons) fluxes keV energies from radiation belts ionizing the upper atmosphere is still absent. The permanent solar monitoring at the main part of the ionizing radiation spectra 0.8-115 (119) nm does not exist. In S.I. Vavilov State Optical Institute (SOI) the apparatus for the Space Solar Patrol (SSP) has been developed in the period 1996-2005 years which includes multiyear experience of developing such apparatus. The base of this apparatus is the use of unique detectors of ionizing radiation – the open secondary electron multipliers, which are "solar blind" to near UV, visible and IR radiations of the Sun, and new methodology of these solar spectroradiometric absolute measurements. These are the problems in the theoretical models of transformation of the solar flare energy and corpuscular preipitation into the microwave ionospheric radiation. Finally, this is the main problem of present day natural science: the physical mechanism of the solar–terrestrial links as applied to the explanation of the detected correlations in the Sun–biosphere and the Sun–weather systems. A unified novel physical (radiooptical) trigger resonance mechanism for controlling the proc-esses in the lower atmosphere and biosphere (including human being), dependent on the level of solar and geomagnetic activity and related to the ionospheric microwave radiation, has been considered.
Keywords: Physics; Optics